Environmentally-friendly technology for rapid identification and quantification of emerging pollutants from wastewater using infrared spectroscopy - Quintelas, Cristina (2020)
Supplementary material related to this article can be found, in theonline version, at doi:https://doi.org/10.1016/j.etap.2020.103458.